2022
DOI: 10.3390/ijms232315304
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analyses Reveal That Fullerol Improves Drought Tolerance in Brassica napus L

Abstract: Carbon nanoparticles have potential threats to plant growth and stress tolerance. The polyhydroxy fullerene—fullerol (one of the carbon nanoparticles) could increase biomass accumulation in several plants subjected to drought; however, the underlying molecular and metabolic mechanisms governed by fullerol in improving drought tolerance in Brassica napus remain unclear. In the present study, exogenous fullerol was applied to the leaves of B. napus seedlings under drought conditions. The results of transcriptomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Transcriptomic and metabolomic analyses have shown that flavonoid accumulation is important to improve drought tolerance in B . napus ( Xiong and Ma, 2022 ). An increase in phenolic content in rapeseed tested under water scarcity has been shown in several studies ( Son et al., 2020 ; Okafor et al., 2022 ; Morsi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic and metabolomic analyses have shown that flavonoid accumulation is important to improve drought tolerance in B . napus ( Xiong and Ma, 2022 ). An increase in phenolic content in rapeseed tested under water scarcity has been shown in several studies ( Son et al., 2020 ; Okafor et al., 2022 ; Morsi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The iron-chelating properties and RSA of flavonoids are closely related; iron is chelated by the flavonoid and ROS are subsequently scavenged by the flavonoids (Kejik et al, 2021;Agraharam et al, 2022). Transcriptomic and metabolomic analyses have shown that flavonoid accumulation is important to improve drought tolerance in B. napus (Xiong and Ma, 2022). An increase in phenolic content in rapeseed tested under water scarcity has been shown in several studies (Son et al, 2020;Okafor et al, 2022;Morsi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Raffinose, melibiose, stachyose, and sucrose are all oligosaccharides involved in galactose metabolism. The oligosaccharides are energetic and structural substances that can serve as carbon sources for plant growth and development [ 38 40 ]. Salt stress down-regulated the soil sucrose metabolism and reduced the production of sugars, which adversely affected plant growth [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Samadi et al 81 , single-walled carbon nanotubes at low concentrations (25, 50, 100 μg/ml) stimulated the synthesis of bioactive compounds of thyme (Thymus daenensis), the development of its callus, and antioxidant activity. These nanoparticles activated antioxidant enzymes, namely polyphenol oxidase, phenylalanine-ammonia-lyase, dehydrogenase and peroxidase.…”
Section: Stress Resistance Of Various Types Of Plants After the Actio...mentioning
confidence: 99%